On Two-parameter Dynamical Systems and Applications (Journal of Sciences, Islamic Republic of Iran)
In this note some useful properties of strongly continuous two-parameter semigroups of operators are studied, an exponential formula for two-parameter semigroups of operators on Banach spaces is obtained and some applied examples of two-parameter dynamical systems are discussed